Paraffin an Overview - Samir Soliman, Fathi (IntechOpen, 2020)
Paraffin waxes make up the majority of commercial waxes. Waxes are characterized by the carbon number, hardness, crystal shape, composition, and molecular weight. These characteristics determine the condition of separating the wax. Paraffin wax is widely used in different industries such as ink, paper, cosmetics, ceramics using powder injection molding and energy storage as phase change materials. Consumption of wax products has increased in the world; especially for food, pharmaceutical products, cosmetics, as well as specialty products. The increase of profitability of wax production will lie in the improvement of blending and modification techniques for macro and micro-crystalline waxes used as the base materials.